2022
DOI: 10.1002/adfm.202202226
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Origin of Ultra‐Low Conductivity in SrTiO3 Thin Films: Sr Vacancies and Ti on A‐Sites Cause Fermi Level Pinning

Abstract: Different SrTiO 3 thin films are investigated to unravel the nature of ultralow conductivities recently found in SrTiO 3 films prepared by pulsed laser deposition. Impedance spectroscopy reveals electronically pseudo-intrinsic conductivities for a broad range of different dopants (Fe, Al, Ni) and partly high dopant concentrations up to several percent. Using inductively-coupled plasma optical emission spectroscopy and reciprocal space mapping, a severe Sr deficiency is found and positron annihilation lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Understanding the impact of strain and interfaces is key for the development of more efficient and sustainable materials for SOFC applications [101][102][103][104][105][106][107][108][109][110]. The intriguing study of Garcia-Barriocanal et al [4] determined that in nanostructured SrTiO 3 /YSZ/SrTiO 3 heterostructures, there is colossal conductivity.…”
Section: Interfaces and Strainmentioning
confidence: 99%
“…Understanding the impact of strain and interfaces is key for the development of more efficient and sustainable materials for SOFC applications [101][102][103][104][105][106][107][108][109][110]. The intriguing study of Garcia-Barriocanal et al [4] determined that in nanostructured SrTiO 3 /YSZ/SrTiO 3 heterostructures, there is colossal conductivity.…”
Section: Interfaces and Strainmentioning
confidence: 99%
“…16 While cationic off-stoichiometry in SrTiO 3 lms has been extensively studied for low-temperature resistive switch properties, its inuence on photocatalytic or photo-electrocatalytic properties related to water splitting has received less attention. 17,18 Kato et al reported improved photocatalytic activity with excess strontium in SrTiO 3 lms, attributing this effect to the reduction of SrO defects acting as electron/hole recombination centers. 19 Yamada et al further corroborated this behaviour, demonstrating enhanced hydrogen production with a Sr/Ti ratio of 1.15.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of A-and B-site non-stoichiometry originates from the central role of Mn atoms in the electronic transport properties [13]. In SrTiO 3 , both A and B site vacancies produce a negative effect on electronic conductivity [16,17]. However, robust magnetic order can also be stabilized in the presence of cationic nonstoichiometry, as found for antisite defects at the interface between LaAlO 3 /SrTiO 3 [18] and in the presence of Ti-O vacancy clusters in SrTiO 3 [19].…”
Section: Introductionmentioning
confidence: 99%